1987
DOI: 10.1002/ana.410220208
|View full text |Cite
|
Sign up to set email alerts
|

Platelet membrane abnormality in Alzheimer's disease

Abstract: Fluorescence studies of membrane fluidity were conducted double-blind using platelet and red cell membranes prepared from 24 demented patients with probable Alzheimer's disease and 36 neurologically healthy subjects. The fluidity of the hydrocarbon and lipid-aqueous interface regions of cell membranes was determined at 37 degrees C by fluorescence spectroscopy using the lipid probes 1,6-diphenyl-1,3,5-hexatriene (DPH) and 1-[4-(trimethylamino)phenyl]-6-phenyl-1,3,5-hexatriene (TMA-DPH), respectively. The rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The significance of this finding is not fully understood. However, Zubenko et al (1987a) report that the group of AD patients with increased platelet membrane fluidity suffer from earlier onset of symptoms and their illness is more rapidly progressive. Zubenko et al (1988) reported that AD patients with raised platelet membrane fluidity had more first-degree relatives with the condition compared with those who had normal platelet membrane fluidity.…”
Section: Rcceived20 September 1989mentioning
confidence: 93%
See 2 more Smart Citations
“…The significance of this finding is not fully understood. However, Zubenko et al (1987a) report that the group of AD patients with increased platelet membrane fluidity suffer from earlier onset of symptoms and their illness is more rapidly progressive. Zubenko et al (1988) reported that AD patients with raised platelet membrane fluidity had more first-degree relatives with the condition compared with those who had normal platelet membrane fluidity.…”
Section: Rcceived20 September 1989mentioning
confidence: 93%
“…Our group has confirmed this (Hicks et a/., 1987) and shown that in this respect A D patients differ from cases of multi-infarct dementia, in which slight but not significant changes are found. Platelet membrane fluidity is not altered in mania or depression (Zubenko et a/., 1987a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial assessments of the specificity of this platelet membrane characteristic are promising. The increase in platelet membrane fluidity associated with Alzheimer disease was not found in platelets from patients with depression [Zubenko et al, 1987d], a common cause of reversible dementia in the elderly; mania [Zubenko and Cohen, 19851, which may also be accompanied by a secondary dementia; or multi-infarct dementia [Hicks et al, 19871. Several lines of evidence have suggested that the platelet membrane abnormality may result from a dysregulation in the biogenesis or turnover of internal membranes [Zubenko et a]., 1987c, f].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that they had discovered a biological subtype of AD. AD patients with the abnormality have an earlier age of onset and deteriorate more rapidly than those without [7], Zubenko and Teply [8] assessed PMF in 15 patients and 10 controls over a 12-month period. No significant changes took place in individual subjects suggesting that it was a stable biological marker.…”
Section: Introductionmentioning
confidence: 99%